The smart grid concept applied to an industrial electrical system - Isidro Fraga Hurtado; Julio Rafael Gómez Sarduy; Percy Rafael Viego Felipe; Vladimir Sousa Santos; Enrique Ciro Quispe Oqueña (Institute of Advanced Engineering and Science, 2021)
Smart grids can be considered as a concept that integrates electrical, automatic control, information, and communication technologies. This concept constitutes a fundamental complement in the integration of renewable energy sources in electrical power systems. Although its application is fundamentally framed in transmission and distribution networks, it could also be implemented in industrial electrical systems. This article aims to analyze the advantages of implementing solutions based on smart grids in the industrial sector. Likewise, the results of its implementation in the large industry in the province of Cienfuegos, Cuba are presented. Specifically, reactive compensation, voltage, and demand management controls were integrated into a Supervision, Control, and Data Acquisition system forming a smart grid. It is shown that, in industries where infrastructure and equipment conditions exist, it is possible to successfully implement solutions with the functionalities and benefits inherent to smart grids.